2017
DOI: 10.1016/j.jclepro.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact of the typical heavy pig production in Italy

Abstract: The Italian pig sector is mainly focused on the production of heavy pigs used for the traditional drycured hams. At slaughter a minimum of 160 kg and 9 months age are required to comply with the production specifications of the ham consortia. Advancing livestock age and increasing fat deposition negatively affect feed conversion ratio, which is one of the main determinants of meat production environmental impact. The aim of the study was to provide a first evaluation of the environmental impact potentials of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 20 publications
9
30
0
Order By: Relevance
“…This feature that is so inherent to the dehesa is the one differentiating these systems from those in the research available on pig's CF, which are intensive systems, such as that of Arrieta and González [64] who found a CF value of 5.14 and 5.17 ton CO 2 eq/ton LW in paddocks and of 6.06 and 6.04 ton CO 2 eq/ton LW in confinement. Other papers such as that of Bava et al [76] in Italy, found that for traditional ham-producing intensive pig farms, the CF calculated for six farms yielded an average of 4.25 ± 1.03 kg CO 2 eq/kg of live weight. The results reported in this paper take into account the GHG emissions attributed to soy and its transport.…”
Section: Discussionmentioning
confidence: 85%
“…This feature that is so inherent to the dehesa is the one differentiating these systems from those in the research available on pig's CF, which are intensive systems, such as that of Arrieta and González [64] who found a CF value of 5.14 and 5.17 ton CO 2 eq/ton LW in paddocks and of 6.06 and 6.04 ton CO 2 eq/ton LW in confinement. Other papers such as that of Bava et al [76] in Italy, found that for traditional ham-producing intensive pig farms, the CF calculated for six farms yielded an average of 4.25 ± 1.03 kg CO 2 eq/kg of live weight. The results reported in this paper take into account the GHG emissions attributed to soy and its transport.…”
Section: Discussionmentioning
confidence: 85%
“…In recent years, environmental impacts of traditional pig production were estimated by several authors [9,[11][12][13][14][15]. The values (Table 6) Consumption of natural resources (chestnuts, acorns and grass) in LCA was only previously considered by Monteiro et al [15] who calculated the emissions from grazing in different systems using local breeds.…”
Section: Environmental Impacts Of Iberian Traditional Pig Production mentioning
confidence: 99%
“…Recent studies focusing on alternative systems, such as organic [7][8][9][10] or traditional pig production [11,12] highlighted that such systems usually have higher impacts than conventional ones. Indeed, they use more compound feeds than conventional systems and fatten pigs to a heavier live weight of elder pigs at slaughter.…”
Section: Introductionmentioning
confidence: 99%
“…The Italian pig sector is mainly focused on the production of heavy pigs, with higher environmental impacts than light pigs. Bava et al (2017) reported a wide variability in the environmental impact categories considered in 5 commercial farms of Northern Italy; for instance, GWP ranged from 2.7 to 5.8 kg CO 2 eq/kg LW of heavy pigs, as compared to an average of 3.1 kg CO 2 eq/kg LW of light pigs calculated from 12 studies reported by the authors. In the heavy pig production, feeds, especially protein sources, have the highest impact and some feeding strategies, such as lowering the dietary crude protein according to the physiological phase and supplementing diets with amino acid, should be implemented (Galassi et al 2010;Schiavon et al 2015).…”
Section: Is017 Environmental Impact Of Animal Productionmentioning
confidence: 97%